SENIOR STUDENTS IN VIRTUAL SPACES; THE TREASURE WITHIN - Lipphardt, Anne-Marie; Escuder-Mollon, Pillar; Adell, J.; Cabedo, S.; Esteller-Curto, R.; et al. (ICERI2015 Proceedings, 2015)
Virtual learning spaces are offered to students to acquire competences and skills regardless of time and space. Even the most usual configuration is the blended learning (virtual and physical teaching mixed), educational institutions also offer 100% virtual learning, mainly to adults in very specific subjects in specialization courses, or other job skills subjects. Even we are aware of the limitations of full virtual learning, it is necessary to acknowledge the enormous advantages it provides, increasing the access of people to education (mostly if those life in rural areas, or disabled). Furthermore, it is also worth mentioning that nowadays, because of the great extend of technology in everyday life, the virtual socialization deserves as much attention as the real life socialization. Senior students are enrolled in educational institutions mainly because of personal motivations (not because of job skills or competitiveness) and they attend to courses because they want to keep active and up-to-date, sharing the time with other classmates, enjoying and learning from this experience. This interaction is reached thanks to physical learning environments, for this reason it is not usual to offer full virtual learning spaces, furthermore when statistically senior citizens are not so ICT skilled as younger (Information and Communication Technologies, that is mainly computer and internet use). The Senior Citizens' University (SCU), started in the course 2011/2012 a pilot curse (using Moodle) with 30 students (senior learners over 55), after this experience, each year the number of subjects and students have been increasing reaching to 12% (that is 114 learners) of the total students from the SCU (in the course 2014/2015 954 students were enrolled in the SCU). Each of the subjects lasts for a semester (45 months) This papers aims to show the results of the use of virtual learning to senior citizens, the difficulties that have appeared and how we tried to solve them year after year. We consider that the virtual teaching is now consolidated with enough quality as a viable approach for senior citizens that do not have possibilities to attend real classes, or that want to use computer mediated learning (a e-inclusion characteristic) Specially remarkable has been noted in teaching-learning process; it has increased in complexity enormously, allowing senior learners to acquire competences difficult to reach in real classrooms; therefore we recommend its implementation by other educational institutions focused on seniors. We show in the paper how the senior learners acquired competences not only related to the content of the subject (that usually was related to history and society areas) but new ways of communication, collaboration, learning and sharing using the ICT. Their feedback (using qualitative research) and also the teachers’ experience has showed the impact the participation in this kind of education had in their technological attitudes and competences. This kind of teaching, when designed based on senior learners needs and requirements, implementing instructional, constructivism, and connectivism pedagogies, showed that made them to learn the course content, but also learn to share, learn to do and learn to learn in the information age society. The results of this research are framed in the “European home learning service for seniors association” (http://ehlssa.odl.org/) KA2 Erasmus + Strategic partnership projec
Keywords: senior; virtual learning; elderly; pedagogy; gerontology; blended learning; moodle